Family communication in efforts to prevent COVID-19 transmission in Indonesia - Tayo, Yanti; Utamidewi, Wahyu; Nursanti, Siti; Mayasari; Zainal Abidin (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study aims to determine family communication to prevent COVID-19. This study uses descriptive qualitative research methods by collecting interview data. This study shows that family communication used by parents and children is very useful in preventing the spread of COVID-19 in Kerrawang Regency. The process of delivering messages related to the dangers of COVID-19 by parents can change children's understanding and behaviour so that preventive actions occur. This research contributes in the form of recommendations to every family so that they can comply with health protocols and always socialise with family members and the community to get used to healthy living by opening airflow in every room in the house, regulating interactions by using masks and keeping a distance in activities at home and outside the house.